Transcriptomes of Ralstonia solanacearum during Root Colonization of Solanum commersonii - Puigvert, Marina; Guarischi-Sousa, Rodrigo; Zuluaga, Paola; Coll, Núria S.; Macho, Alberto P.; Setubal, João C.; Valls, Marc (Frontiers in Plant Science, 2017)
Bacterial wilt of potatoes –also called brown rot– is a devastating disease caused by the vascular pathogen Ralstonia solanacearum that leads to significant yield loss. As in other plant-pathogen interactions, the first contacts established between the bacterium and the plant largely condition the disease outcome. Here, we studied the transcriptome of R. solanacearum UY031 early after infection in two accessions of the wild potato Solanum commersonii showing contrasting resistance to bacterial wilt. Total RNAs obtained from asymptomatic infected roots were deep sequenced and for 4609 out of the 4778 annotated genes in strain UY031 were recovered. Only 2 genes were differentially-expressed between the resistant and the susceptible plant accessions, suggesting that the bacterial component plays a minor role in the establishment of disease. On the contrary, 422 genes were differentially expressed (DE) in planta compared to growth on a synthetic rich medium. Only 73 of these genes had been previously identified as DE in a transcriptome of R. solanacearum extracted from infected tomato xylem vessels. Virulence determinants such as the Type Three Secretion System (T3SS) and its effector proteins, motility structures and reactive oxygen species (ROS) detoxifying enzymes were induced during infection of S. commersonii. On the contrary, metabolic activities were mostly repressed during early root colonization, with the notable exception of nitrogen metabolism, sulphate reduction and phosphate uptake. Several of the R. solanacearum genes identified as significantly up-regulated during infection had not been previously described as virulence factors. This is the first report describing the R. solanacearum transcriptome directly obtained from infected tissue and also the first to analyze bacterial gene expression in the roots, where plant infection takes place. We also demonstrate that the bacterial transcriptome in planta can be studied when pathogen numbers are low by sequencing transcripts from infected tissue avoiding prokaryotic RNA enrichment.